Prediction of difficult airway by thyromental height test- a comparison with modified mallampati test. - Nurullah, Md; Alam, Md Shah; Hossen, Mahmud; Shahnawaz, Marufa (Bangladesh Journal of Medical Science, 2018)
Background: Management of airway is central to the Practice of anaesthesia. One of the anaesthesiologist fundamental roles is to maintain a patent airway at a all times.Maintaining a patent airway is essential for adequate oxygenation and ventilation and failure to do so, even for a brief period of time, can be life threatening. Recently, thyromental height test (TMHT) has been proposed as one of the highly sensitive and specific bedside tests to predict difficult airway. Objective: To assess the predictivity of thyromental height test in comparison to modified Mallampati test. Methods: This cross sectional study was carried out in Anesthesiology department of ISMCH during the period of January, 2015 to December, 2016. A total number of 139 consecutive patients scheduled for elective surgical procedure under general anaesthesia requiring intubation having American Society of Anesthesiologists grading I-II. Statistical analyses of the results were obtained by SPSS-20. Sensitivity, specificity, accuracy, positive predictive value and negative predictive value of Thyromental height test and Modified mallampati scoring in diagnosis of difficult airway were calculated. Results: Most (74.4) of the patients belonged to age ≤50 years. Male to female ratio was 1.01:1. Majority 91(65.5%) patients had thyromental height of ≥50 mm. In the diagnosis of difficult airway, Thyromental height test was 92.7% sensitivity, 93.5% specificity, 93.5% accuracy and 85.4% positive predictive values, 97.8% negative predictive value, 13.1% positive likelihood ratio, 0.05 negative likelihood ratio. On the other hand Modified mallampati scoring was 48.8% sensitivity, 92.7% specificity, 79.1% accuracy, 75.0% positive predictive values, 80.2% negative predictive value, 6.7% positive likelihood ratio, 0.55 negative likelihood ratio for prediction of difficult airway. Conclusions: It can be concluded that the thyromental height is useful diagnostic modality for predicting difficult airway. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.455-461